Välfärd och vishet i samhällskroppen - om GNH som stämgaffel för samhällen, Smart Cities och ekobyar - Rosengren, Anna (Socialmedicinsk tidskrift, 2018)
Summary The aim of this paper was to open the question about how we may measure and maintain welfare in a wise way. We got some tentative answers, such as the importance of wisdom as a foundation for measuring and maintaining welfare. GNH was found to be a very wise model for holistic welfare, working as a tuning fork for the SDG:s and other models. We found that neither Smart Cities nor Eco Villages offer a complete strategy on their own. We proposed an integrated dialogue in society, where many perspectives and levels may be part of a ‘mulit-level governance’ and where horizontal as well as vertical transformation may take place. We also proposed, as the profound agenda for all political dialogue and action, a wise vision for all Earthlings. Abstrakt på svenska Syftet med denna uppsats är att öppna frågan om hur vi kan mäta och behålla välfärd på ett vist sätt. Det betonar vikten av vishet som grund för att mäta och upprätthålla välfärd. GNH föreslås som en vis modell för holistisk välfärd och som en stämgaffel för SDG: s och andra modeller. Vi undersöker också Smart Cities och Eco Villages som praktiska strategier för välfärd och föreslår en integrerad dialog i samhället, där många perspektiv och nivåer kan vara en del av en "multi-level governance" och där både horisontell och vertikal omvandling kan äga rum. Jag föreslår också, som en grundläggande agenda för all politisk dialog och handling, en vis vision för alla jordbor. Abstract in English The aim of this paper is to open the question about how we may measure and maintain welfare in a wise way. It emphasizes the importance of wisdom as a foundation for measuring and maintaining welfare. GNH is suggested as a wise model for holistic welfare, working as a tuning fork for the SDG:s and other models. We also examine Smart Cities and Eco Villages as practical strategies for welfare and propose an integrated dialogue in society, where many perspectives and levels may be part of a ‘mulit-level governance’ and where horizontal as well as vertical transformation may take place. We also propose, as the profound agenda for all political dialogue and action, a wise vision for all Earthlings.